Quantitative Psychological Research - Clark-Carter David (Routledge - Taylor & Francis Group, 2019)
This book provides a step - by - step guide to research that students and researchers will find extremely useful. This fourth edition also provides constistently outstanding coverage of the core principles of psycholgical research. Preface, Acknowledgements, Introduction, The Methods Used in Psychological Research, Choice of Topic and Measures and Research Design, The Preliminary Stages of Research, Variables and the Validity of Research Designs, Research Designs and Their Internal Validity, Methods, Asking Question I: Interviews and Surveys, Asking Question II: Measuring Attitudes and Meaning, Observation and Content Analysis, Data and Analysis, Scales of Measurement, Summarising and Describing Data, Going Beyond Description, Samples and Populations, Analysis of Differences Between a Single Sample and a Population, Effect Size and Power, Parametric and Non - Parametric Tests, Analysis of Differences Between Two Levels of an Independent Variable, Preliminary Analysis of Designs with One Independent Variable with More than Two Levels, Analysis of Designs with More than One Independent Variable, Analysis of Covariance (ANCOVA), Screening Data, Exploratory Factor Analysis (EPA), Multivariate Analysis.